Peningkatan Pemahaman Manajemen Operasional Pada Proses Produksi - Ririn Uke Saraswati; Sarmin Sarmin; Arrofie Darmawan; Sony Sonjaya; Fenika Bunga Prawida Suwanto; Khairil Anwar; Sandi Arif Setiadi; Winda Neri Sari (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
: Operational management is a field of management that has a focus in production or services using special tools and techniques to complete the production. Participants can implement knowledge about the way of production process that is the combination of one material with the other so that it becomes a product, the purpose of operational management, benefits, planning, strategy and challenges in the production process within the company. To gain a deeper knowledge of how production processes within the enterprise then it is necessary to understand the operational control of the process of production. Thus, through this seminar, we were conducted in the Aula of the School of Economic Sciences of Ekadharma Indonesia by inviting three sources that were very competent in its field and which were followed by 42 public participants among them consisting of class XII students of the school. In the seminar activities in addition to adding knowledge about the production process can also be discussed together as well as inserted some ice breaking to get some interesting prizes during the event. To see how enthusiastic the participants were, we used some suggestions and criticisms from some of the participants with a review method and a double choice that contained excellent good, good, pretty good, and bad. And it can be concluded that 66.1% of the participants thought that the seminar was very useful.